Decitabine Sensitizes the Radioresistant Lung Adenocarcinoma to Pemetrexed Through Upregulation of Folate Receptor Alpha - Wang, Yuqing; Huang, Jie; Wu, Qiong; Zhang, Jingjing; Ma, Zhiyuan; Zhu, Lucheng; Xia, Bin; Ma, Shenglin; Zhang, Shirong (Frontiers in Oncology, 2021)
Chemotherapy is the backbone of subsequent treatment for patients with lung adenocarcinoma (LUAD) exhibiting radiation resistance, and pemetrexed plays a critical role in this chemotherapy. However, few studies have assessed changes in the sensitivity of LUAD cells to pemetrexed under radioresistant circumstances. Therefore, the objectives of this study were to delineate changes in the sensitivity of radioresistant LUAD cells to pemetrexed and to elucidate the related mechanisms and then develop an optimal strategy to improve the cytotoxicity of pemetrexed in radioresistant LUAD cells. Our study showed a much lower efficacy of pemetrexed in radioresistant cells than in parental cells, and the mechanism of action was the significant downregulation of folate receptor alpha (FRα) by long-term fractionated radiotherapy, which resulted in less cellular pemetrexed accumulation. Interestingly, decitabine effectively reversed the decrease in FRα expression in radioresistant cells through an indirect regulatory approach. Thereafter, we designed a combination therapy of pemetrexed and decitabine and showed that the activation of FRα by decitabine sensitizes radioresistant LUAD cells to pemetrexed both in vitro and in xenografts. Our findings raised a question regarding the administration of pemetrexed to patients with LUAD exhibiting acquired radioresistance and accordingly suggested that a combination of pemetrexed and decitabine would be a promising treatment strategy.